Does the Mustahik Demographic and Socio-Cultural Affect to the Successful of Poverty Alleviation? - Budi Trianto; Saparuddin Siregar; M. Yasir Nasution (International Journal of Zakat, 2020)
Zakat institutions have a very important role in alleviating poverty in a country through various programs that they make. One of the poverty alleviation programs carried out by zakat institutions is mustahik empowerment in the economic field. In socio-cultural and demographic terms, surely every mustahik who participates in the program has differences. By involving 105 respondents from four zakat organizations in Pekanbaru, this study aims to find out whether mustahik demography and socio-cultural have influenced the success of the mustahik empowerment program in alleviating poverty by using a logistic regression approach. In the demographic variables, the finding shows only two from six variables that have an effect on the success in eradicating mustahik poverty, namely the household members and employment status with the odds ratio of each variable of 1,540 and 2,385. The other variables that did not significantly influence were gender, education level, age and location of residence. Meanwhile, for the three socio-cultural variables, the finding is only one variable that affects the success of the empowerment program, namely family culture with an odds ratio of 2,861. Variable society habits and religiosity do not significantly influence. The results of this study have implications for the empowerment program that in carrying out the mustahik empowerment program, zakat institutions must pay attention to socio-cultural and mustahik demographics in order to get maximum results.